Knowledge and information sharing practices among multidisciplinary university dormitory residents: exploring the influence of gender, academic discipline, and degree level / Md. Liton Ali - Ali, Md. Liton (Faculty of Information Management, 2023)
This study investigated the culture of Knowledge and Information Sharing (KIS) among university dormitory students using a quantitative research design based on a survey. Data were collected from 16 dormitories and residential halls in a large-scale public university in Bangladesh, with 343 responses utilized for data analysis. The findings revealed that students engage in sharing knowledge and in-formation with their peers, with male students and those pursuing postgraduate degrees sharing more frequently. The majority of students perceived KIS as crucial for their career development. However, there were significant differences in attitudes towards KIS between male and female students, with male students dis-playing a more positive attitude. The study highlights the importance of fostering a cultural environment that encourages openness and leads to new opportunities and expansion.